Interpretation battles on Google and YouTube: Islamic and non-Islamic views on rulings about apostasy and theft - Lino Klevesath (Frontiers in Political Science)
Among the believers of Islam, no central, universally accepted institution exists that could decide authoritatively on the interpretations of Islamic norms. Today, internet users encounter an enormous diversity of Muslim and non-Muslim authority claims to interpret the norms of Islam. But which type of norm interpretation dominates when users search on Google and YouTube for information on the Islamic rulings on apostasy and theft? Drawing on the literature on the concept of authority and its application to the religious field as well as on the theory on religious markets, the method of a manual search on Google and YouTube was chosen to analyze the top 15 search results on each platform on the topic of apostasy in Islam as well as the issue of theft. The analysis revealed that neither conservative Islamic perspectives nor secular content nor other types of interpretation prevail unchallenged. The wide variety of interpretations of the most diverse Islamic commandments by the most diverse actors (secular and Muslim, including followers of a rigid Sunni Islam as well as liberal Muslims) ensures that divergent interpretations are always just a few clicks away. Searches on Google and YouTube on the Islamic ruling on apostasy revealed that lots of content tried to challenge its validity from a secular view infused with Islamic scripture-based reasoning. The search results for content on Google and YouTube on the Islamic ruling on theft showed a prominence of conservative Muslim positions defending the legitimacy of the punishment of amputation which is incompatible with the principles of liberal democracy. However, the liberal Muslim position renouncing the punishment was also present, as well as anti-Muslim videos. It is argued that governments as well as actors of civil society that want to improve the cohesion of society and stimulate support for liberal democracy among Muslims need to think about ways how liberal interpretations of Islamic norms that are compatible with democracy can be made more visible online—without infringing on the freedom of religion or strangling the religious market.